KIPRAH SYAHRUDDIN TUANKU KATIB BANDARO DALAM BIDANG KEAGAMAAN DARI NAGARI PAINGAN KECAMATAN SUNGGAI LIMAU KABUPATEN PADANG PARIAMAN TAHUN ( 1967 -2013 ) - Frandinata, Siska - (Pendidikan Sejarah, 2014)
This thesis talks about how Tuanku Syahruddin Katib Bandaro in developing Syattariyah ideology inPariaman especially in Korong Paingan Guguak Kuranji Hilir Village. This study needs to do, because we cansee his way in develop Syattariyah ideology. To easier this study, i wrote formulate the problem as follow : HowSyahruddin Tuanku Katib Bandaro role in developingislamic ways in general and developing Syattariyahideology in korong Paingan Guguak Kuranji Village Sunggai Limau Regency. Problem statement in this studyis how Tuanku Syahruddin Katib Bandaro role in developing Syattariyah ideology in Korong Paingan GuguakKuranji Hilir Village, Sungai Limau regency. The aim of this study is to see how Tuanku Syahruddin KatibBandaro Basa role in developing Syattariyah ideology. Study method that used is suitable with history methodthrough these steps : First, Heuristik is collecting soure data in interview in litaratom form, Second, sourecritique, is to trip the souries those had been collected througt internal and external critique. Third, interpretationis explaning facts by connecting the each fact that suitable with historical event that fourth Historiography ispresenting the result of study in thesis form. From the result of this study we know that Tuankun SyahruddinKatib Bandaro in developing Islamic way and developing Syattariyah ideology has important role in developingIslamic way and Syattariyah ideology by doing speech and retitation to congregation by buil Mata Air Mosquethat located in Kampung Tangah, Korong Paingan, Guguak Kuranji Hilir village as a worshiping place, speechand religion activity. Trough this Tuanku Syahruddin developing Syattariyah ideology.